Growth of Dendrobium Oryen Orchids at the acclimatization stage by providing organic materials to the planting media and spraying foliar fertilizer - Sinaga, A. O.; Ganefianti, D. W.; Romeida, A.; Armadi, Y.; Herawati, R. (International Journal of Agricultural Technology, 2025)
The study's findings indicated that the leaf quantity and breadth variables are influenced by the frequency of foliar fertilizer applications and the addition of organic material to the planting medium. Adding organic material was significantly impacted the root length and leaf count variables, while the other seven were unaffected. The treatment of fertilization frequency did not affect every variable. Fertilizing once every six days with organic material drawn from Moringa leaf litter produced the most leaves while fertilizing once every six days with organic material derived from coffee husks generated the broadest leaves. The longest orchid roots are generated when organic material from Lamtoro leaf litter is placed in an orchid-growing environment.